Incidence and outcomes of hospitalized acute ischemic stroke patients with subsequent ST-segment-elevation myocardial infarction - Mahmood, Arhum; Ang, Song Peng; Qadeer, Yusuf Kamran; Hassan Virk, Hafeez Ul; Tangsrivimol, Jonathan Alan; Riaz, Iqra; Wang, Zhen; Alam, Mahboob; Strauss, Markus; Krittanawong, Chayakrit (Frontiers in Cardiovascular Medicine, 2025)
BackgroundPatients admitted with acute ischemic stroke (AIS) may experience accompanying acute ST-Segment myocardial infarction after AIS. The cardiovascular risks, incidence, complications, and outcomes of acute STEMI in patients hospitalized with AIS remains underexplored.MethodsWe evaluated 2,804,819 patients that presented with AIS who were listed in the National Inpatient Sample from 2016 to 2021. AIS and STEMI were defined according to the ICD-10 Diagnostic Codes. Patients with Non-STEMI were excluded. The risk of specific complications and outcomes were expressed as percentages. Multivariable logistic regression analysis was used to examine the association of STEMI with a primary outcome of mortality and secondary outcomes. The temporal trend of both the incidence of STEMI after AIS as well as the mortality rate between 2016 and 2021 were expressed as percentages over time.ResultsOf the total (n = 2,804,819) patients with AIS, 6,550 also had STEMI diagnosed during the hospitalization. Of these, 1,635 (24.96%) died in the STEMI group and 86,810 (3.10%) died in the group without STEMI. All of the secondary outcome measures were significantly associated with a diagnosis of STEMI. STEMI was associated with mortality [OR 7.43 (95% CI, 6.44–8.57); P < 0.001], cardiogenic shock [OR 29.64, (95% CI, 22.64–38.81); P < 0.001], cardiac arrest [OR, 7.76 (95% CI, 6.01–10.03); P < 0.001], and AKI [OR 1.96 (95% CI, 1.72–2.23); P < 0.001] among other complications. When assessed yearly, the temporal trend of STEMI among AIS patients showed a decrease in frequency from about 0.3% in 2016 to about 0.2% in 2021. Furthermore, comparing the mortality between AIS patients with and without STEMI showed a significant difference with a higher mortality in the AIS with STEMI population.ConclusionsPatients admitted with acute ischemic stroke who had STEMI have a significant mortality increase compared to those who did not have STEMI. They also had a significant increase in secondary complications including cardiac arrest, cardiogenic shock, AKI, and need for further medical interventions. Temporally, we have seen a decrease in STEMI after AIS over the interval.